2022
DOI: 10.3390/molecules27072283
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bicyclo[3.1.0]hexane-Based A3 Receptor Ligands: Closing the Gaps in the Structure–Affinity Relationships

Abstract: The adenosine A3 receptor is a promising target for treating and diagnosing inflammation and cancer. In this paper, a series of bicyclo[3.1.0]hexane-based nucleosides was synthesized and evaluated for their P1 receptor affinities in radioligand binding studies. The study focused on modifications at 1-, 2-, and 6-positions of the purine ring and variations of the 5′-position at the bicyclo[3.1.0]hexane moiety, closing existing gaps in the structure–affinity relationships. The most potent derivative 30 displayed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…To further validate whether GT949 truly activates EAAT2, radioligand uptake assays were performed. The protocols for the dose response curve (DRC) and kinetic assay (Figure ) were adapted from previous work done in our lab . TFB-TBOA (10 μM) was taken as a negative control in all radioligand uptake assays.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To further validate whether GT949 truly activates EAAT2, radioligand uptake assays were performed. The protocols for the dose response curve (DRC) and kinetic assay (Figure ) were adapted from previous work done in our lab . TFB-TBOA (10 μM) was taken as a negative control in all radioligand uptake assays.…”
Section: Resultsmentioning
confidence: 99%
“…The protocols for the dose response curve (DRC) and kinetic assay (Figure 3) were adapted from previous work done in our lab. 23 TFB-TBOA (10 μM) was taken as a negative control in all radioligand uptake assays. Indeed, TFB-TBOA, which has been described as a nonselective competitive inhibitor, acting on EAAT1, 2, and 3, 18,19 clearly reduced radioligand (L-[3,4-3 H]glutamic acid) uptake in both EAAT2 and EAAT3 (Figure 3), in accordance with the normal signal-to-noise ratio found in the literature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, compounds 21 were tested at 1 μM in radioligand displacement experiments against four subtypes of adenosine receptors, namely, A 1 , A 2A , A 2B , and A 3 , as previously reported ( Figure S7 and Table S3 , Supporting Information ). 55 In addition, compounds were screened at 10 μM against P2X7R purinergic receptors in an YO-PRO-1 uptake assay 56 ( Figure S8 , Supporting Information ). Performed experiments, however, revealed that synthesized 5,6-dihydro-5-azapurines 21 have little to no affinity/inhibitory activity toward these five purinergic receptors.…”
Section: Resultsmentioning
confidence: 99%